Fe-doped Li3VO4 as an excellent anode material for lithium ion batteries: Optimizing rate capability and cycling stability. (10th June 2019) - Liu, Xiaoqing; Li, Guangshe; Zhang, Dan; Chen, Dandan; Wang, Xiyang; Li, Baoyun; Li, Liping
Abstract: Li3 VO4 has been deemed as a promising anode material owing to its high theoretical capacity (592 mA h g −1 ), superior ionic conductivity, and zero strain during charge and discharge process. Nevertheless, its electronic conductivity is low, which has led to an electrochemical performance unfavorable for practical application. In this work, Fe doped Li3 VO4 samples have been synthesized via freeze-drying and heating-treatment procedures. The obtained samples of Li3 V(1-x) Fex O4-δ (x = 0, 0.005, 0.01, 0.02) show a slight lattice expansion with an increase in Fe content. When evaluated for lithium storage capacity, Fe doped Li3 VO4 samples exhibited an enhanced electrochemical performance relative to those undoped parent, as represented by an excellent rate capability (213 mA h g −1 at 2000 mA g −1 ), and good cyclic stability (a stable Coulombic efficiency of 98 ± 1% after initial three cycles at 100 mA g −1 ) for Li3 V0.99 Fe0.01 O4-δ . The reasons for these performance improvements are ascribed to the increased electronic conductivity originated from the creation of oxygen vacancy, reduced bandgap, and a rapid Li + ion diffusion process as revealed by X-ray photoelectron spectrum, O K-edge X-ray absorption near edge structure analysis, UV–vis spectroscopy, and electrochemical impedance spectroscopy. The present work provides some hints for designing and synthesizing Li3 VO4 based anode materials with superior electrochemical performance.